2016
DOI: 10.1007/s00330-016-4336-0
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced spectral mammography in recalls from the Dutch breast cancer screening program: validation of results in a large multireader, multicase study

Abstract: ObjectivesContrast-enhanced spectral mammography (CESM) is a promising problem-solving tool in women referred from a breast cancer screening program. We aimed to study the validity of preliminary results of CESM using a larger panel of radiologists with different levels of CESM experience.MethodsAll women referred from the Dutch breast cancer screening program were eligible for CESM. 199 consecutive cases were viewed by ten radiologists. Four had extensive CESM experience, three had no CESM experience but were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
81
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 22 publications
4
81
1
Order By: Relevance
“…Using specific digital subtraction technique, CESM is able to erase the normal mammary gland and highlight the hypervascular lesions with better depiction of their frames and vasculatures. Preliminary studies have confirmed the superior sensitivity and specificity of CESM than conventional digital mammography . And several studies indicated the comparability of CESM to DCE‐MRI for breast cancer detection and diagnosis .…”
Section: Introductionmentioning
confidence: 88%
“…Using specific digital subtraction technique, CESM is able to erase the normal mammary gland and highlight the hypervascular lesions with better depiction of their frames and vasculatures. Preliminary studies have confirmed the superior sensitivity and specificity of CESM than conventional digital mammography . And several studies indicated the comparability of CESM to DCE‐MRI for breast cancer detection and diagnosis .…”
Section: Introductionmentioning
confidence: 88%
“…In a multireader study of 199 women who underwent CESM during workup an abnormality detected on screening mammography, Lalji et al 5 noted an improvement in the diagnostic parameters of all 10 readers. Mean sensitivity increased from 93% to 96.9% and specificity from 35.9% to 69.7%.…”
Section: Introductionmentioning
confidence: 99%
“…also highlighted the value of CESM as a problem‐solving tool following recall from a breast screening programme. This study found that CESM increased the diagnostic accuracy of readers regardless of level of expertise …”
Section: Case 1 Contrast‐enhanced Spectral Mammography To Localise Amentioning
confidence: 55%
“…They reported that CESM changed the diagnostic and treatment strategy in 21% of their patients . A study by Lalji et al . also highlighted the value of CESM as a problem‐solving tool following recall from a breast screening programme.…”
Section: Case 1 Contrast‐enhanced Spectral Mammography To Localise Amentioning
confidence: 99%
See 1 more Smart Citation